Multiple Low-Grade Fibromyxoid Sarcoma on the Upper Arms with Atypical Histological Presentation - Sadanori Furudate; Taku Fujimura; Yumi Kambayashi; Akira Tsukada; Yukikazu Numata; Setsuya Aiba (Karger Publishers, 2013)
Low-grade fibromyxoid sarcoma (LGFMS) is a rare variant of spindle cell tumor that is composed of collagen-rich and myxoid parts. We describe the case of a 61-year-old Japanese patient with multiple, recurrent LGFMS on the upper arms with atypical histological presentation. In the present case, we resected the tumor several times with a minimal surgical margin, as in Moh's microsurgery. However, this can frequently lead to local recurrence of the tumor. Our case suggested that, regarding mesenchymal tumors with potential of malignancy in the skin, an initial wide excision is indispensable for complete remission of the tumor, even for low-grade malignancy such as LGFMS.